2004
DOI: 10.1158/1078-0432.ccr-04-0951
|View full text |Cite
|
Sign up to set email alerts
|

Pseudolaric Acid B Inhibits Angiogenesis and Reduces Hypoxia-Inducible Factor 1α by Promoting Proteasome-Mediated Degradation

Abstract: Purpose: Pseudolaric acid B (PAB), the naturally occurring diterpenoid isolated from the root bark of Pseudolarix kaempferi Gordon tree (Pinaceae), possesses potent antifungal and pregnancy-terminating effects that may be tightly associated with angiogenesis. This study was to examine its angiogenic inhibition, impact on vascular endothelial growth factor (VEGF) secretion from tumor cells and the possible mechanism of action.Experimental Design: Angiogenesis inhibition was assessed by the human umbilical vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 33 publications
0
68
0
Order By: Relevance
“…Although the involvement of mitogenactivated protein kinase (MAPK) pathway in maintaining the stability of HIF-1a has been contradictory in literature (Richard et al, 1999;Hur et al, 2001), we and others have shown that inhibition of p42/p44 ERKs by PD98059 diminished the stability of HIF-1a (Yoo et al, 2003(Yoo et al, , 2004Li et al, 2004;Zhang et al, 2005). Consistent with the previous results, activation of p42/p44 ERKs as well as stability of HIF-1a was significantly induced under hypoxia and repressed by PD98059 ( Figure 3d) (Yoo et al, 2003(Yoo et al, , 2004Li et al, 2004;Zhang et al, 2005). Similarly, 6-MP increased phosphorylated p42/p44 ERKs, whereas PD98059 decreased the phosphorylation of p42/p44 as well as the protein level of both HIF-1a and Nur77 ( Figure 3d).…”
Section: -Mp Enhances Transcriptional Activity Of Hif-1a Y-g Yoo Et Almentioning
confidence: 98%
“…Although the involvement of mitogenactivated protein kinase (MAPK) pathway in maintaining the stability of HIF-1a has been contradictory in literature (Richard et al, 1999;Hur et al, 2001), we and others have shown that inhibition of p42/p44 ERKs by PD98059 diminished the stability of HIF-1a (Yoo et al, 2003(Yoo et al, , 2004Li et al, 2004;Zhang et al, 2005). Consistent with the previous results, activation of p42/p44 ERKs as well as stability of HIF-1a was significantly induced under hypoxia and repressed by PD98059 ( Figure 3d) (Yoo et al, 2003(Yoo et al, , 2004Li et al, 2004;Zhang et al, 2005). Similarly, 6-MP increased phosphorylated p42/p44 ERKs, whereas PD98059 decreased the phosphorylation of p42/p44 as well as the protein level of both HIF-1a and Nur77 ( Figure 3d).…”
Section: -Mp Enhances Transcriptional Activity Of Hif-1a Y-g Yoo Et Almentioning
confidence: 98%
“…We also found that of the 17 identified antiangiogenic compounds, 4 compounds, namely, pseudolaric acid B, MFTZ-1, 10-hydroxycamptothecin and triptolide, can indirectly inhibit the VEGF-VEGFR axis by decreasing cellular HIF-1α accumulation and thereby reducing VEGF expression and secretion [15][16][17][18][19][20][21] (Figure 1). We define these compounds to be HIF-1α-VEGF axis inhibitors.…”
Section: Hif-1α-vegf Axis Inhibitorsmentioning
confidence: 85%
“…Pseudolaric acid B targets microtubulin and causes its depolymerization [22,23] . Pseudolaric acid B inhibits angiogenesis by reducing the stability of HIF-1α and thereby downregulating the VEGF-VEGFR axis [15,16,18] . However, there has been no direct evidence indicating any association between its antiangiogenic activity and its inhibition of microtubulin [23,24] .…”
Section: Hif-1α-vegf Axis Inhibitorsmentioning
confidence: 99%
“…PAB also showed strong cytotoxic activity. In our collaboration study, this compound was found for the first time to have strong antiangiogenic activity with a unique mode of antitumor action [118][119][120] . A structural modification of PAB was thus conducted, and more than 40 derivatives were prepared in the first round.…”
Section: Miscellaneousmentioning
confidence: 92%